1998
DOI: 10.1097/00004872-199816110-00001
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis and hypertension

Abstract: Genetic and fetal influences appear to have significant effects in determining impaired vascular development as an early cause of essential hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 72 publications
3
62
0
Order By: Relevance
“…These data are consistent with the observation of structural alterations of the microvascular bed in hypertension. 28 Moreover, hypertension was shown to be associated with a profound downregulation of tissue hepatocyte growth factor, which is an essential endothelial growth factor. 29,30 Thus, a paracrine effect induced by increased angiotensin II levels in hypertensive patients could potentially be involved in the regulation of EPC migration.…”
Section: Vasa Et Al Risk Factors and Endothelial Progenitor Cellsmentioning
confidence: 99%
“…These data are consistent with the observation of structural alterations of the microvascular bed in hypertension. 28 Moreover, hypertension was shown to be associated with a profound downregulation of tissue hepatocyte growth factor, which is an essential endothelial growth factor. 29,30 Thus, a paracrine effect induced by increased angiotensin II levels in hypertensive patients could potentially be involved in the regulation of EPC migration.…”
Section: Vasa Et Al Risk Factors and Endothelial Progenitor Cellsmentioning
confidence: 99%
“…First, the angiogenic capacity of serum derived from SHR was less than that from normotensive animals in a chick embryo chorio-allantoic membrane model. 13 Protein levels of key proangiogenic growth factors such as vascular endothelial growth factor (VEGF) and hepatocyte growth factor are also reduced in hypertensive animals. 11,14 Second, previous obser-…”
mentioning
confidence: 99%
“…First, the angiogenic capacity of serum derived from SHR was less than that from normotensive animals in a chick embryo chorio-allantoic membrane model. 13 Protein levels of key proangiogenic growth factors such as vascular endothelial growth factor (VEGF) and hepatocyte growth factor are also reduced in hypertensive animals. 11,14 Second, previous obser-vations that endothelial function is impaired in SHR as well as in patients with essential hypertension imply that the defective endothelial function may contribute to impaired angiogenesis in SHR.…”
mentioning
confidence: 99%
“…21 On the other hand, abnormal angiogenesis has been demonstrated in hypertension. 22,23 Previous studies have demonstrated that hypertensive patients exhibit elevated plasma levels of Ang-1 and Ang-2. 5 Moreover, abnormal indices of angiogenesis in hypertension are correlated with target organ damage 6 and cardiovascular outcome.…”
Section: Discussionmentioning
confidence: 99%